DNA Methylation Dynamics in Atlantic Salmon (Salmo salar) Challenged With High Temperature and Moderate Hypoxia - Beemelmanns, Anne; Ribas, Laia; Anastasiadi, Dafni; Moraleda-Prados, Javier; Zanuzzo, Fábio S.; Rise, Matthew L.; Gamperl, A. Kurt (Frontiers in Marine Science, 2021)
The marine environment is predicted to become warmer and more hypoxic, and these conditions may become a challenge for marine fish species. Phenotypically plastic responses facilitating acclimatization to changing environments can be mediated by DNA methylation through the modulation of gene expression. To investigate whether temperature and hypoxia exposure induce DNA methylation changes, we challenged post-smolt Atlantic salmon (Salmo salar) to increasing temperatures (12 → 20°C, 1°C week-1) under normoxia or moderate hypoxia (~70% air saturation) and compared responses in the liver after 3 days or 4 weeks at 20°C. DNA methylation was studied in six genes related to temperature stress (cirbp, serpinh1), oxidative stress (prdx6, ucp2), apoptosis (jund), and metabolism (pdk3). Here, we report that exposure to high temperature, alone or combined with hypoxia, affected the methylation of CpG sites within different genomic regulatory elements around the transcription start of these temperature/hypoxia biomarker genes. Yet, we uncovered distinct CpG methylation profiles for each treatment group, indicating that each environmental condition may induce different epigenetic signatures. These CpG methylation responses were strongly dependent on the duration of stress exposure, and we found reversible, but also persistent, CpG methylation changes after 4 weeks of exposure. Further, several of these changes in CpG methylation correlated with transcriptional changes, and thus, can be considered as regulatory epigenetic marks (epimarkers). Our study provides insights into the dynamic associations between CpG methylation and transcript expression in Atlantic salmon, and suggests that this epigenetic mechanism may mediate physiological acclimation to short-term and long-term environmental changes.